Brief Image-based Health Behavior Messages for Adolescents and Their Parents - Werch, Chudley (Chad) (2008)
This study tested the efficacy of brief image-based print mediated parent/caregiver and adolescent messages integrating physical activity with alcohol use avoidance. A total of 684 high school students were randomly assigned to either the parent postcard or adolescent flyer arm, with baseline and four-month post-intervention data collections. A significant repeated measures interaction (group × time) was found (F(4,344)=2.48, p=.04), with univariate tests showing less alcohol use frequency and problems (p’s<.05) among adolescents exposed to parent materials. Repeated measures factorial MANOVAs for group × time × prior current drug use were significant, with drug using adolescents receiving parent print messages showing less alcohol initiation and frequency, and marijuana initiation and frequency (p’s<.05). Very brief print materials sent to parents/caregivers may hold some promise for influencing substance use among adolescents, particularly those already using drugs.